Supporting the inclusion and retention of autistic students: Exploring teachers' and paraeducators' use of evidence-based practices in public elementary schools - Locke, Jill; Hernandez, Alyssa M.; Joshi, Mahima; Hugh, Maria L.; Bravo, Alice; Osuna, Anthony; Pullmann, Michael David (Frontiers in Psychiatry, 2022)
Educators in public schools are required to serve students in their least restrictive environment. While many evidence-based practices (EBPs), defined as practices and strategies shown by research to have meaningful effects on outcomes for autistic students are documented in the literature, less is known about EBP use among educators in public schools. Eighty-six general and special education teachers and paraeducators completed a survey about familiarity, training, and EBP use for included autistic children. Across roles, educators reported familiarity (98.8%), use (97.7%), and training (83.7%) in reinforcement. They reported the least familiarity with behavioral momentum (29.1%), training in both video modeling and peer-mediated instruction and intervention (18.6%), and use of video modeling (14.0%). Follow-up interviews (n=80) highlighted mixed understanding of EBP definitions and use. Implications for inclusive education are discussed including autism-specific EBP training within pre-service teacher preparation programs.